2022
DOI: 10.3389/fimmu.2022.901913
|View full text |Cite
|
Sign up to set email alerts
|

Advances on Innate Immune Evasion by Avian Immunosuppressive Viruses

Abstract: Innate immunity is not only the first line of host defense against pathogenic infection, but also the cornerstone of adaptive immune response. Upon pathogenic infection, pattern recognition receptors (PRRs) of host engage pathogen-associated molecular patterns (PAMPs) of pathogens, which initiates IFN production by activating interferon regulatory transcription factors (IRFs), nuclear factor-kappa B (NF-κB), and/or activating protein-1 (AP-1) signal transduction pathways in host cells. In order to replicate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 164 publications
0
7
0
Order By: Relevance
“…To be able to improve prophylactic strategies we will have to further understand the innate and acquired immune responses of birds and find new approaches to stimulate the protective immune responses in a specific way and drive the immune system toward long-lasting memory responses. Certainly, downsides of vaccination have to be considered as they may, especially in the context of insufficient herd immunity, favor immune evasion of pathogens and the development of new variants in the field (202204). This further strengthens the need for vaccines with the potential of the induction of sterile immunity or, at least, the most efficient reduction of pathogen shedding in vaccinated birds.…”
Section: Discussionmentioning
confidence: 99%
“…To be able to improve prophylactic strategies we will have to further understand the innate and acquired immune responses of birds and find new approaches to stimulate the protective immune responses in a specific way and drive the immune system toward long-lasting memory responses. Certainly, downsides of vaccination have to be considered as they may, especially in the context of insufficient herd immunity, favor immune evasion of pathogens and the development of new variants in the field (202204). This further strengthens the need for vaccines with the potential of the induction of sterile immunity or, at least, the most efficient reduction of pathogen shedding in vaccinated birds.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chauss et.al showed that 1,25D promotes anti-inflammatory responses by switching off IFN-γ production from Th1 cells and upregulating IL-10 [ 43 ]. IFN-γ and IFN-β production is essential for effective viral clearance; viruses have mechanisms to evade the IFN responses, and severe COVID-19 is associated with dysregulation of IFN responses [ 44 , 45 , 46 ]. Down-regulation of IFN-β by vitamin D is associated with protection from inflammation in the lung following a virus infection with either influenza or SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted June 30, 2022. ; https://doi.org/10.1101/2022.06.29.498158 doi: bioRxiv preprint of IFN responses [45][46][47]. Down-regulation of IFN by vitamin D is associated with protection from inflammation in the lung following a virus infection with either influenza or SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Chauss et.al showed that 1,25D promotes anti-inflammatory responses by switching off IFN production from Th1 cells and upregulating IL-10 [44]. IFN- and IFN production is essential for effective viral clearance, viruses have mechanisms to evade the IFN responses, and severe COVID-19 is associated with dysregulation of IFN responses [45][46][47]. Down-regulation of IFN by vitamin D is associated with protection from inflammation in the lung following a virus infection with either influenza or SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%